A new approach for thermal performance calculation of cross-flow heat exchangers - Navarro, H. A.; Cabezas-Gomez, L. (Elsevier B.V., 2005)
A new numerical methodology for thermal performance calculation in cross-flow heat exchangers is developed. Effectiveness-number of transfer units (epsilon-NTU) data for several standard and complex flow arrangements are obtained using this methodology. The results are validated through comparison with analytical solutions for one-pass cross-flow heat exchangers with one to four rows and with approximate series solution for an unmixed-unmixed heat exchanger, obtaining in all cases very small errors. New effectiveness data for some complex configurations are provided. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: thermal effectiveness; NTU; cross-flow heat exchangers; numerical simulation